Ancient DNA perspectives on pathogen evolution in domestic animals - Dimopoulos, EA (2021)
Pathogens, animals (domesticated or not) and humans have intertwined evolutionary trajectories for millennia now, with this relationship intensifying after the Neolithic Demographic Transition and its subsequent epidemiological transition that increased the exposure of animal populations to pathogenic reservoirs. Incorporating the temporal dimension in the study of disease evolution requires the incorporation of ancient pathogen DNA data in phylogenetic and population genetic analyses, which is not a simple task. Limited DNA survival and DNA damage, however, have hindered the search for ancient pathogens. For these reasons the accurate identification of microbial species from archaeological samples is integral and has the potential to provide an unprecedented perspective on the evolutionary history of major diseases that have affected humans and domestic animals. In the first chapter of this thesis I propose a novel analytical method for metagenomic identifications, HAYSTAC, which can also be applied for direct hypothesis testing regarding the presence of pathogens in metagenomic samples. By employing a clear probabilistic model for species identification from shotgun sequencing DNA data, along with incorporating additional algorithmic steps for taxonomic result validation, robust metagenomic identifications from sequencing data generated from archaeological samples become possible, with a significantly lower false positive rate when compared to pre-existing and established methods. In the second chapter of this thesis I used HAYSTAC to screen more than one thousand archaeological and modern chicken samples for Marek’s Disease Virus (MDV), a devastatingly virulent virus threatening the modern poultry industry. Following the DNA sequencing of archaeological chicken samples positive for MDV, I reconstructed the genomes of these ancient strains and compared them to modern ones. Through a time dependent phylogenetic reconstruction approach, I identified the possibility that modern MDV strains are evolving at an accelerated rate compared to ancient ones, with modern highly virulent strains possibly evolving from a potentially non-virulent (ancient) form (prior to 1907) of MDV, a finding that can have a significant impact on improving the health status of domestic chicken population globally. In the third chapter of this thesis, I examine if the process of domestication has had an impact on the disease burden of domestic pigs and dogs, by applying HAYSTAC. By applying hypothesis-driven species identification methods, I focused on screening animal derived metagenomes for zoonotic bacterial pathogens. Since many of the causative agents of these zoonotic diseases became prevalent in a post-industrial context, the results of this approach will be able to offer insights into how human activity has reshaped the landscapes of both the natural environment and animal diseases.